E0016 Tongxinluo reduces myocardial ischaemia-reperfusion injury and no-reflow by stimulating the expression and phosphorylation of eNOS via PKA pathway. (17th November 2010) - Li, Xiangdong; Yang, Yuejin; Geng, Yong-Jian; Jin, Chen; Hu, Feng-Huan; Zhao, Jing-Lin; Zhang, Hai-Tao; Cheng, Yu-Tong; Qian, Hai-Yan; Wang, Lin-Lin; Zhang, Bao-Jie; Wu, Yi-Ling
Abstract : Objective: To investigate whether oral administration of Tongxinluo (TXL), a traditional Chinese medicine, at a single low loading dose 1 h before myocardial ischaemia can attenuate ischaemia-reperfusion injury by regulating endothelial nitric oxide synthase (eNOS) via protein kinase A (PKA) pathway. Methods and results: In 90-min ischaemia and 3-h reperfusion model, Minipigs were randomly assigned to four groups (n=8 in each group): (1) Sham; (2) Control; (3) TXL: 0.05 g·kg −1 of TXL was gavaged 1 h prior myocardial ischaemia; (4) TXL+H-89 (1.0 μg·kg −1 ·min −1, an inhibitor of PKA). TXL significantly decreased creatine kinase (CK) activity, reduced the infarct size from 78.5% to 59.2% and no-reflow area from 48.6% to 9.5% (p<0.05), while H-89 completely abolished the reduction of CK activity and necrosis size, and partially diminished the reduction of no-reflow size. TXL enhanced the PKA activity in ischaemic myocardium, increased the expression of PKA, Thr 198 p-PKA and Ser 635 p-eNOS in no-reflow area, and upregulated the expression of eNOS and Ser 1179 p-eNOS in reflow area. H-89 repressed the enhancement of PKA activity and the upregulation of eNOS and Ser 635 p-eNOS, but without great inhibition on the expression of PKA and Thr 198 p-PKA in no-reflow area, and even stimulated the expression of Ser 635 p-eNOS in reflow area. Conclusion: Pretreatment with single low loading dose of TXL 1 h before myocardial ischaemia reduces myocardial no-reflow and ischaemia-reperfusion injury by upregulating the expression of eNOS and p-eNOS (Ser 1179 and Ser 635), and this effect is partially mediated by PKA pathway.